PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS DAN PENDEKATAN PEMBELAJARAN TEKNIS TERHADAP HASIL BELAJAR KETERAMPILAN PASSING DAN STOPING - Ricky Fernando; Kamarudin Kamarudin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
This research is about to study the effect of tactical and technical approach to learning result of passing andstoping skill. The results of this study is expected to serve as an alternative solution in order to improve thequality of learning soccer. The method used in this research is the experimental method. The population in thisresearch is the first semester 1 student of FKIP UIR as many as 160 people. The number of samples are 16people with sampling technique using Cluster Random Sampling. Time of research is for 2 months, the numberof treatment 16 times meeting, with frequency 1 week 3 times. The author's chosen instrument is a passing andstoping skills test in football. for physical education students FKIP UIR soccer skills test (early and final test ofpassing and stoping skills). Based on the result of the analysis, it can be concluded: (1) The learning approachusing tactical approach gives influence to the skill of passing and stoping the student of FKIP UIR physicaleducation (2) The learning approach using tactical approach gives influence to the skill of passing and stopingthe student of FKIP UIR mask. (3) using a tactical approach and a technical approach are equally influential onpassing and stoping skills of UF FKIP students. However, the learning approach using tactical approach hasmore significant impact than the technical learning approach.PENGARUH PENDEKATAN PEMBELAJARAN TAKTIS DANPENDEKATAN PEMBELAJARAN TEKNIS TERHADAP HASIL BELAJARKETERAMPILAN PASSING DAN STOPING